Association between inflammatory bowel disease and bullous pemphigoid: a population-based case–control study - Yi-Ju Chen; Chao-Kuei Juan; Yun-Ting Chang; Chun-Ying Wu; Hsiu J. Ho; Hsiao-Ching Tseng (Scientific Reports, 2020)
Abstract The coexistence of inflammatory bowel disease (IBD) and bullous pemphigoid (BP) has been reported. No large-scale study to date has explored the relationship between these diseases. This population-based case-control study examined the association between IBD and BP by using a nationwide database. A total of 5,263 BP patients and 21,052 age- and gender-, hospital visit number-matched controls were identified in the National Health Insurance Research Database of Taiwan (1997–2013). Demographic characteristics and comorbidities including IBD were compared. Logistic regression was conducted to examine the predicting factors for BP. The mean age at diagnosis was 74.88 years and 54.3% of subjects were male. BP patients tended to have more cardiovascular risk factors, autoimmune and neurologic comorbidities, and hematologic cancers than matched controls. There were 20 cases of IBD (0.38%), mostly ulcerative colitis (N = 17, 0.32%) among BP patients, compared to 33 IBD cases (0.16%) among controls (p < 0.001). Ulcerative colitis was found to be significantly associated with BP [adjusted odds ratio (OR) 3.60, 95% confidence interval (CI) 1.91–6.77, p < 0.001] on multivariate analysis. Treatment for IBD was not associated with BP development. Information about diet, lifestyle, alcohol consumption, and smoking habit was not available. We concluded that UC is independently associated with BP.